Bacterial Communities in Neonatal Feces are Similar to Mothers' Placentae. (2015) - Dong, Xu-Dong; Li, Xiao-Ran; Luan, Jian-Jun; Liu, Xiao-Feng; Peng, Juan; Luo, Yi-Yong; Liu, Chen-Jian
Abstract : BACKGROUND: The gut microbiota plays an important role in human health. It is essential to understand how the composition of the gut microbiota in neonates is established. OBJECTIVES: To investigate the nature of the microbial community in the first feces of newborn infants compared with the mothers' placentae and vaginas. METHODS: One infant who was delivered via Cesarean section was compared with an infant who was delivered vaginally. Bar-coded pyro-sequencing of 16S ribosomal RNA genes was used to investigate the bacterial community composition and structure of each site. RESULTS: Neonatal feces of both infants had similar bacterial communities, and they were similar to the mother's placenta regardless of the method of delivery. The vaginal bacterial community differed between the two mothers, but not different sites within the vagina. The bacteria in the neonatal feces and the mothers' placentae demonstrated considerably higher diversity compared with the vaginas. The family Lactobacillaceae dominated in the vaginal samples, while the most abundant family in the fecal and placental samples was Micrococcineae . CONCLUSIONS: These results may provide new directions for the study of infant gut microbial formation.